'A Revolutionary Voice': Analysing Maxine Peake's Northern stardom in Silk and Room at the Top. Issue 2 (1st October 2016) - Gorton, Kristyn; Peirse, Alison
This article explores how Maxine Peake's explicit and directly articulated social conscience – specifically in terms of class, gender and Northernness – can be explored in television drama, and what this might say about her 'Northern Stardom' in our contemporary cultural climate. Our central case studies are the series Silk (2011–2014) and mini-series Room at the Top (2012), both chosen as recent productions that explicitly engage with politics but in quite different ways. In the case of Silk this is foregrounded as a courtroom drama, while Room at the Top's 1950s' setting demonstrates the way working-class men and women were able to break free of expectations around their gender and social standing – but at a cost. Peake is presented in popular culture as a rarity, a socially aware, politically active Northern actor who is able to break free of a Northern stereotype; at the same time, we will argue, as an actor she brings an honesty/emotion to the roles she plays that both chime with audience expectations of the 'strong' Northern woman and yet allow her to expose the fragility and anxiety inherent to this persona.